Electron energy relaxation under terahertz excitation in (Cd1−xZnx)3As2 Dirac semimetals - Galeeva, Alexandra V.; Krylov, Ivan V.; Drozdov, Konstantin A.; Knjazev, Anatoly F.; Kochura, Alexey V.; Kuzmenko, Alexander P.; Zakhvalinskii, Vasily S.; Danilov, Sergey N.; Ryabova, Ludmila I.; Khokhlov, Dmitry R. (Beilstein Journal of Nanotechnology, 2017)
We demonstrate that measurements of the photo-electromagnetic effect using terahertz laser radiation provide an argument for the existence of highly conductive surface electron states with a spin texture in Dirac semimetals (Cd1−xZnx)3As2. We performed a study on a range of (Cd1−xZnx)3As2 mixed crystals undergoing a transition from the Dirac semimetal phase with an inverse electron energy spectrum to trivial a semiconductor with a direct spectrum in the crystal bulk by varying the composition x. We show that for the Dirac semimetal phase, the photo-electromagnetic effect amplitude is defined by the number of incident radiation quanta, whereas for the trivial semiconductor phase, it depends on the laser pulse power, irrespective of wavelength. We assume that such behavior is attributed to a strong damping of the interelectron interaction in the Dirac semimetal phase compared to the trivial semiconductor, which may be due to the formation of surface electron states with a spin texture in Dirac semimetals.
Keywords: Dirac semimetal; photo-electromagnetic effect; terahertz radiation; topological insulator